ملامح المذهب الشخصي في قانون العقوبات الفلسطيني رقم (74) لسنة 1936 المطبَّق في قطاع غزة - أحمد أسامة, حسنية; ماهر, أسامه مسعود (Revue jurisprudence; No 17 (2018): مجلة الاجتهاد القضائي, 2018)
يعتبر وجه الاتفاق ونقطة الالتقاء بين المذهبان  الشخصي والموضوعي في اعترافهما بأن الخطر الذي يهدد الحق أو المصلحة المحمية بموجب القانون هو علة التجريم والعقاب، ويقران كذلك بأن السياسة الجنائية لا تعتد بالنية الإجرامية وحدها. وإنما يتطلب التعبير عنها بأفعال مادية. ورغم ذلك فإن نقطة الاختلاف بين المذهبان  تتمثل في تحديد مصدر الخطر: فأنصار المذهب الموضوعي يرونه كامناً في أفعال الجاني، وأنصار المذهب الشخصي يرونه كامناً في نية الجاني وشخصيته. هذا الاختلاف في التحليل والتأصيل ستترتب عليه نتائج هامة على مستوى مضمون وأحكام قانون العقوبات فالشروع مثلاً يتطلب طبقاً للمذهب الموضوعي أفعالاً خطرة في ذاتها، ولكنه يقوم عند أنصار المذهب الشخصي بكل فعل يكشف – على نحو قاطع – عن خطورة شخصية الجاني، وهذا يعني أن للفعل في المذهب الأول قيمة ذاتية في حين لا تعدو قيمته في المذهب الثاني عن أنه قرينة على خطورة الشخصية الإجرامية. وبذلك يكون العقاب طبقاً للمذهب الشخصي ذو نطاق أوسع  من نطاق ذلك في المذهب الموضوعي، ويمكن أن نفسر ذلك من خلال أن الكثير من الأفعال قد تكون غير خطرة في ذاتها فلا يعتد بها المذهب الموضوعي، ولكنها كافية للكشف عن خطورة الجاني فيعتد بها المذهب الشخصي. هذا الخلاف والالتقاء هو مكمن هذا البحث الذي حاول أن يرصد ملامح المذهب الشخصي وحده دون الموضوعي من خلال أحكام قانون العقوبات الفلسطيني رقم 74 لسنة 1936. الكلمات المفتاحية: المذهب الشخصي، الاعتبار الشخصي، الغلط في الإباحة، النتيجة المحتملة، العلاقة السببية، الشروع. Abstract  : The point of agreement and the point of convergence between personal and objective doctrines is their recognition that the threat to the right or interest protected by law is the reason of criminalization and punishment, and that criminal policy is not concerned to only criminal intents but rather to express them by material acts. Nevertheless, the point of difference between the two doctrines is to determine the source of danger: the proponents of the objective doctrine see it as inherent in the actions of the offender, and supporters of the personal doctrine see it as inherent in the intention and character of the offender. This difference in analysis and rooting will have important consequences at the level of content and the provisions of the Penal Code. For example, attempting to crime according to objective doctrine requires dangerous acts in itself, but it is at the supporters of the personal doctrine in any act that reveals - definitively - the seriousness of the character of the offender, The first doctrine has intrinsic value, while its value in the second doctrine is not presumed to be a presumption of the seriousness of the criminal personality. Thus, punishment according to personal doctrine has a broader scope than that in objective doctrine. This can be explained by the fact that many acts may be non-dangerous in themselves. The objective doctrine is not reliable, but it is sufficient to reveal the seriousness of the offender . This controversy is the basis of this research, which tries to monitor the features of the personal doctrine alone without objectivity through the provisions of the Palestinian Penal Code No. 74 of 1936 . Keywords:   personal doctrine, Personal consideration,  Causality,   The criminal result.